Policy change and women's and men's earnings around divorce: Evidence from the German maintenance reform - Michaela Kreyenfeld; Sarah Schmauk; Katharina Wrohlich; Daniel Brüggmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
This paper examines the gendered impact of divorce on earnings and the role of the social policy context in shaping this relationship. In particular, it focuses on a policy reform enacted in Germany in 2008 that overturned previous ex-spousal support rules. Data come from the administrative records of the German Public Pension Fund. Drawing on a fixed- effects model, we study the behaviour of women and men who separated between 2004 and 2011 (n=21,617 divorces). We find that women's earnings increased throughout the divorce process. This effect was slightly more pronounced after the reform than before. In contrast to women's earnings, men's earnings declined throughout the divorce process. The reform seems to have somewhat mitigated this negative divorce effect. The paper also shows heterogeneous effects across regions. While divorce had strong effects on women's and men's earnings in West Germany, it did not change the earning patterns of East German men and women either before or after the reform. The paper concludes by discussing avenues for post- separation policies from a gender perspective.
Keywords: J12; J22; K36; 330